Thermal Performance Enhancement of Epoxy/MWCNT Nanocomposites (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
This study investigates the preparation and characterization of epoxy/MWCNT nanocomposites with varying concentrations (0.1, 0.3, and 0.6 wt%) of multi-walled carbon nanotubes (MWCNTs). MWCNTs were dispersed using ultrasonication, and the resulting dispersions were incorporated into the epoxy matrix. The prepared nanocomposites were characterized using X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), and thermal analysis. XRD analysis revealed information on the alignment, distribution, and crystal structure of MWCNTs within the epoxy matrix, while FESEM images provided insights into the dispersion quality, interfacial interaction, and overall quality of the nanocomposites. Thermal analysis showed that increasing MWCNT concentration led to a general increase in the glass transition temperature (Tg) of the polymeric composite. The results demonstrated that the addition of MWCNTs to epoxy can enhance mechanical, thermal, and electrical properties by forming a rigid network and restricting polymer chain molecular mobility. However, achieving uniform MWCNT dispersion in the epoxy matrix is critical for optimizing these benefits and ensuring the optimal performance of the nanocomposites.